RANCANGAN DESAIN UI/UX UNTUK WEBSITE TOKO SAYUR ERMIWATI MENGGUNAKAN METODE DESIGN THINKING - M. Agel Lerian; M. Ihsan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of information technology encourages business actors to utilize digital media in improving services and expanding marketing. Toko Sayur Ermiwati still uses conventional sales methods so that product promotion, information delivery, and transaction processes have not run optimally. This research aims to design the User Interface (UI) and User Experience (UX) of the Toko Sayur Ermiwati website using the Design Thinking method. The research stages include Empathize, Define, Ideate, Prototype, and Testing with data collection through observation, interviews, and literature studies. The results of the research are in the form of a website prototype with login features, product catalog, ordering, admin dashboard, product management, transactions, and reports. The resulting design prioritizes ease of navigation, responsive display, and better user experience to support the effectiveness of services and digital transformation of Toko Sayur Ermiwati.